Dual Nakamura model for primary and secondary crystallization applied to nonisothermal crystallization of poly(ether ether ketone). Issue 10 (18th August 2021) - Seo, Jiho; Zhang, Xiaoshi; Schaake, Richard P.; Rhoades, Alicyn M.; Colby, Ralph H.
Abstract: Non‐isothermal crystallization kinetics has been traditionally predicted using the Nakamura crystal growth model, which is an integral form of the Avrami equation under the assumption that the non‐isothermal kinetics can be explained using a series of infinitesimal isothermal steps. However, the Nakamura model often overpredicts crystal fraction near the end of crystallization because of ignoring slower secondary crystallization kinetics. In this study, the dual Nakamura model is proposed to capture both primary and secondary crystallization kinetics of poly(ether ether ketone) (PEEK). First, non‐isothermal crystallization kinetics of PEEK is monitored at five constant cooling rates of 10, 30, 50, 70, and 90 K/min via differential scanning calorimetry. The dual Nakamura model, which contains a smaller secondary Avrami exponent ( n s ) to account for the secondary crystallization, is fitted to the exothermal heat flow curves. The dual Nakamura model successfully describes the final stage of crystallization at all cooling rates by reducing the crystal growth dimension from n p  = 3 for primary crystallization to n s ≅ 1 . Abstract : Non‐isothermal crystallization kinetics has been traditionally predicted using the Nakamura crystal growth model. However, the Nakamura model often overpredicts crystal fraction near the end of crystallization because of ignoring slower secondary crystallization kinetics. In this study, the dual Nakamura model is proposed to capture both primary and secondary crystallization kinetics of poly(ether ether ketone).